Crystal structure of langbeinite-related Rb0.743K0.845Co0.293Ti1.707(PO4)3. (March 2015) - Strutynska, Nataliia Yu.; Bondarenko, Marina A.; Ogorodnyk, Ivan V.; Baumer, Vyacheslav N.; Slobodyanik, Nikolay S.
No abstract available